Analysis of Value Added Tax Application on Electronic Commerce Transaction in Digital Economy System in Indonesia - Nurhadi; Wibowo, Agung Satryo; Darmawan, Didit; Negara, Dharma Setiawan; Hardyansah, Rommy (Journal of Social Science Studies, 2023)
This research discusses the implementation of Value Added Tax (VAT) on electronic commerce transactions in Indonesia, which faces major challenges related to the mismatch between existing tax regulations and the rapid development of the digital sector. Although the government has issued regulations such as Minister of Finance Regulation No. 48/PMK.03/2020 to regulate the imposition of VAT on electronic commerce, its implementation is still limited by the lack of understanding of business actors and supervision constraints on cross-border transactions. This research uses a normative juridical approach to explore the gap between legal theory and practice in the field. The results show that the existing tax system has not been able to keep pace with the development of the digital trade sector, especially in regulating cross-border transactions and simplifying the tax administration process. For this reason, improvements are needed in terms of regulation, supervision, and education to business actors so that the application of VAT on electronic commerce transactions can be more effective. The findings also provide recommendations for utilizing technology to improve tax monitoring and remittance systems, as well as the need for stricter regulations regarding digital platforms that operate across countries.